2008
DOI: 10.1097/cnd.0b013e31818e9510
|View full text |Cite
|
Sign up to set email alerts
|

Electrodiagnostic and Clinical Aspects of Guillain-Barré Syndrome: An Analysis of 142 Cases

Abstract: Motor conduction blocks and temporal dispersion could be observed from days 3 and 5 onward, respectively. Progression of motor conduction slowing in AIDP was most impressive in the median nerves. Varying affection of deep tendon reflexes, cranial nerves, and cerebrospinal fluid albuminocytological dissociation can also help make a distinction between AIDP and acute motor axonal neuropathy. Sural sparing, a marker of demyelinating neuropathy, is more commonly seen in later than in early stages of AIDP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…In our study, the patients were classified into AIDP or AMAN based on the existing electrodiagnostic criteria. [10]…”
Section: Methodsmentioning
confidence: 99%
“…In our study, the patients were classified into AIDP or AMAN based on the existing electrodiagnostic criteria. [10]…”
Section: Methodsmentioning
confidence: 99%
“…In Indian series the incidence of AIDP and AMAN are virtually equal although AMAN is more common in younger patients. [8] There seems to be a slight preponderance of AIDP in studies by Gupta et al [9] and by Meena et al (unpublished data from NIMS, Hyderabad). Available Indian literature indicates a peak incidence between June–July and Sept–October.…”
Section: Epidemiologymentioning
confidence: 97%
“…The most common variant of GBS was AIDP followed by AMAN. Other studies from different parts of the world have reported 80-90 per cent frequency from Europe and the USA1819 and Indian studies reporting 48.8 to 85.2 per cent202122. A large study from northern India comprising 328 patients reported AIDP in 73.8 per cent patients and better outcome compared to AMAN6.…”
Section: Discussionmentioning
confidence: 95%